Children and COVID‐19: Microbiological and immunological insights. Issue 10 (30th July 2020) - Buonsenso, Danilo; Sali, Michela; Pata, Davide; De Rose, Cristina; Sanguinetti, Maurizio; Valentini, Piero; Delogu, Giovanni
Abstract: Since its first description in China, severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) has spread worldwide being declared a pandemic by the World Health Organization. More than 10.3 million people have been infected and more than 506 000 people died. However, SARS‐CoV‐2 had a lower impact on the pediatric population. Only about 1% to 2% of infected people are children and few deaths under the age of 14 are described so far. In this article, we discuss microbiological and immunological characteristics of SARS‐CoV‐2 infection in children highlighting the main differences from adult SARS‐CoV‐2 infection.